Potassium Hydroxide Solubility Test to Determine Protein Quality of Soybean Meal - Mahesh, M. S.; Puri, Prashant M.; Tripathi, S. P. (Indian Journal of Animal Nutrition, 2017)
The present study investigated the quality of commercially available soybean meals (SBM) using potassium hydroxide (KOH) solubility test. A total number of 12 samples from different traders were procured over a period of eight months and analysed for chemical composition and KOH solubility. It was observed that mean CP content and KOH soluble protein was 46.1 and 74.7%, respectively. Furthermore, 25% of the samples failed to comply acceptable KOH soluble protein range of 70-85% thereby indicating excess heat treatment. This cautions for ensuring strict quality control of SBM before incorporating into compound feeds especially for poultry, pigs and perhaps pre-ruminants.